High-resolution 3D ultrastructural analysis of developing mouse neocortex reveals long slender processes of endothelial cells that enter neural cells - Wilsch-Bräuninger, Michaela; Peters, Jula; Huttner, Wieland B. (Frontiers in Cell and Developmental Biology, 2024)
To gain a 3D insight into the ultrastructure of the developing neocortex, we have analyzed the embryonic mouse neocortex by serial block face scanning electron microscopy (SBF-SEM).Here, we report a first set of findings that focus on the interaction of blood vessels, notably endothelial tip cells (ETCs), and the neural cells in this tissue. A key observation was that the processes of ETCs, located either in the ventricular zone or in the subventricular zone / intermediate zone, can enter, traverse the cytoplasm, and even exit, apical progenitors, basal progenitors, and newborn neurons, via deep plasma membrane invaginations of the host cell.More than half of the ETC processes were found to enter the neural cells. Striking examples of this ETC process "invasion" were (i) protrusions of apical progenitors or newborn basal progenitors into the ventricular lumen that contained an ETC process inside, and (ii) ETC process-containing protrusions of neurons that penetrated other neurons. Our observations reveal a -so far unknown -complexity of ETC -neural cell interaction.